2022
DOI: 10.18203/2394-6040.ijcmph20222926
|View full text |Cite
|
Sign up to set email alerts
|

Insights of Rashtriya Bal Swasthya Karyakram: a strength, weaknesses, opportunities, and threats analysis

Abstract: Over 400 million children between 0 and 18 live in India, making it the world's largest country for children. Out of every 100 newborns, 6 to 7 are estimated to have birth abnormalities and a significant fraction of children experience nutritional inadequacies and developmental impairments. Rashtriya Bal Swasthya Karyakram (RBSK), a programme created to enhance the health of children from birth to 18 years of age through early identification, prevention, and management of 30 health conditions under the 4Ds, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Mukherjee et al [ 11 ] concluded that the number of children identified for delay and disability has increased since the inception of the scheme. However, some states, such as Maharashtra and Odisha, faced issues with implementation, infrastructure constraints, and limited resources [ 14 ]. Furthermore, the scheme does not cater to private schools in India, which constitute 49% of children in urban areas and 21% in rural areas [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mukherjee et al [ 11 ] concluded that the number of children identified for delay and disability has increased since the inception of the scheme. However, some states, such as Maharashtra and Odisha, faced issues with implementation, infrastructure constraints, and limited resources [ 14 ]. Furthermore, the scheme does not cater to private schools in India, which constitute 49% of children in urban areas and 21% in rural areas [ 15 ].…”
Section: Introductionmentioning
confidence: 99%